2001
DOI: 10.1074/jbc.m105599200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Pak1 by the p35/Cdk5 Kinase Affects Neuronal Morphology

Abstract: The small GTPase Rac and its effectors, the Pak1 and p35/Cdk5 kinases, have been assigned important roles in regulating cytoskeletal dynamics in neurons. Our previous work revealed that the neuronal p35/Cdk5 kinase associates with Pak1 in a RacGTP-dependent manner, causing hyperphosphorylation and down-regulation of Pak1 kinase activity. We have now demonstrated direct phosphorylation of Pak1 on threonine 212 by the p35/ Cdk5 kinase. In neuronal growth cones, Pak1 phosphorylated on Thr-212 localized to actin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 61 publications
4
112
1
Order By: Relevance
“…This also reveals that between Rac1 and its effector Pak1, several molecules, including transcriptional factors such as NFATc1 and kinases such as CDK6/4, are recruited in the phosphorylation and activation of Pak1 by its modulator Rac1. In support of a role of CDKs in the phosphorylation and activation of Pak1, previous studies have also shown that CDK5, a neuronal specific CDK, mediates Pak1 phosphorylation and activation during neurite outgrowth (50). Besides, this study reveals for the first time that NFATc1, via its involvement in the mediation of Pak1 activation, plays a role in F-actin cytoskeletal remodeling.…”
Section: Discussionsupporting
confidence: 78%
“…This also reveals that between Rac1 and its effector Pak1, several molecules, including transcriptional factors such as NFATc1 and kinases such as CDK6/4, are recruited in the phosphorylation and activation of Pak1 by its modulator Rac1. In support of a role of CDKs in the phosphorylation and activation of Pak1, previous studies have also shown that CDK5, a neuronal specific CDK, mediates Pak1 phosphorylation and activation during neurite outgrowth (50). Besides, this study reveals for the first time that NFATc1, via its involvement in the mediation of Pak1 activation, plays a role in F-actin cytoskeletal remodeling.…”
Section: Discussionsupporting
confidence: 78%
“…CDK5 is an apical instigator in many neuronal cell death cascades 15,14,27,17 and phosphorylates various proteins implicated in cytoskeletal organization. 28,29 In addition, CDK5 has previously been shown to be implicated in various cellular events involving turnover of biological membranes, for example cell migration, axonal outgrowth or endocytosis. 10,27,11 These cellular functions also require cytoskelettal structures, and we considered that, albeit a simplifying view, the process of mitochondrial fission shares mechanistic similarities with the cleavage of cell membranes during 'pinching off' of endocytotic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant GST-Nb1 1-144 and GST-Nb1A95 1-144 proteins were produced and subjected to radioactive kinase assay as described previously (Rashid et al, 2001). …”
Section: Kinase Assaysmentioning
confidence: 99%